The role of gut microorganisms and metabolites in intracerebral hemorrhagic stroke: a comprehensive review - Wen, Xin; Dong, Hao; Zou, Wei (Frontiers in Neuroscience, 2024)
Intracerebral hemorrhagic stroke, characterized by acute hemorrhage in the brain, has a significant clinical prevalence and poses a substantial threat to individuals’ well-being and productivity. Recent research has elucidated the role of gut microorganisms and their metabolites in influencing brain function through the microbiota-gut-brain axis (MGBA). This article provides a comprehensive review of the current literature on the common metabolites, short-chain fatty acids (SCFAs) and trimethylamine-N-oxide (TMAO), produced by gut microbiota. These metabolites have demonstrated the potential to traverse the blood–brain barrier (BBB) and directly impact brain tissue. Additionally, these compounds have the potential to modulate the parasympathetic nervous system, thereby facilitating the release of pertinent substances, impeding the buildup of inflammatory agents within the brain, and manifesting anti-inflammatory properties. Furthermore, this scholarly analysis delves into the existing dearth of investigations concerning the influence of gut microorganisms and their metabolites on cerebral functions, while also highlighting prospective avenues for future research.